Putting Off Until Tomorrow: Academic Procrastination, Perfectionism, and Fear of Failure - Subhan Ajrin Sudirman; Faisal Adnan Reza; Nur Aisyiah Yusri; Rina Rina; Mucktarr Bah (Universitas Muhammadiyah Yogyakarta, 2023)
Academic procrastination among students is becoming more widespread. The lack of time management causes this issue. Students without clear schedules or priorities can be more easily tempted to put off work or important academic assignments when managing their time. Other psychological factors contributing to this academic procrastination behavior are perfectionism and fear of failure. This study aims to empirically prove the relationship between perfectionism and fear of failure in academic procrastination. The method used in this research was correlational quantitative with a population of 153 students. The instruments used included academic procrastination, perfectionism, and fear of failure scales. The analysis technique was multiple linear regression. The results showed a positive correlation between perfectionism and fear of failure in academic procrastination, with an F score of 29.133 and a significance value of 0.001. This study also concluded that it is important for students to learn time management strategies, deal with anxiety effectively, and better understand failure and mistakes as part of the learning process. It is also important to emphasize that high standards can motivate success but must be balanced with good mental and physical health. They must not come at the expense of an individual’s mental well-being.